Quantification of auditory sensory gating in mouse models of tinnitus and psychiatric disorders - Boerner, Bárbara Ciralli (2022)
This thesis investigates auditory sensory gating, a neural mechanism of filtering repetitive and irrelevant sounds from the environment, which is important to prevent information overload at higher cortical areas. Disturbances in sensory gating are associated with several psychiatric disorders, such as schizophrenia and attention-deficit hyperactivity disorder, while its role in auditory phantom perception is less studied. In the first chapter, sensory gating alterations in an animal model of tinnitus are described. The objective of this study was to first investigate whether noise-exposure interferes with auditory gating, and second, if nicotine or natural extracts of cannabis would improve or impair auditory pre-attentional processing in noise-exposed mice. Mice were implanted with electrode arrays to assess auditory event-related potentials (aERPs) in the dorsal hippocampus in response to paired sound clicks in a noise-induced tinnitus mouse model. Alterations of aERPs under nicotine (1.0 mg/kg, intraperitoneal - i.p.) or THC-rich cannabis extract (100 mg/kg, i.p.) were evaluated (in isolation or in combination). Our results show that mice with behavioral evidence of tinnitus display auditory gating of repetitive click, but with larger amplitudes and longer latencies of the aERP negative peak (N40) component compared to sham exposed animals. In contrast, no difference was observed in the positive peak (P80) amplitude and latency between groups or treatments. The combination of cannabis extract and nicotine improved auditory gating ratio in mice with noise-induced tinnitus by strongly increasing the first N40 click amplitude but without altering the second click response amplitude. Furthermore, the increased latency of the N40 component suggests altered temporal processing of triggered attention in mice with tinnitus due to an increased sensitivity to the exposure to cannabis extract. In summary, nicotine and cannabis extract treatments were shown to alter sensory gating in mice with behavioral evidence of tinnitus, indicating that the altered central plasticity in tinnitus is more sensitive to the combined actions on the cholinergic and the endocannabinoid systems. In the second chapter, knockout mice for an orphan solute carrier gene, Slc10a4 were screened for alterations in sensory gating. The Slc10a4 -/- mice, which lack a monoaminergic and cholinergic associated vesicular transporter protein and show accumulation of dopamine in the striatum synaptic clefts, were investigated for the identification of a potential animal model for psychiatric disorders. Auditory ERPs in response to paired sound clicks were recorded by intrahippocampal single shank multichannel electrodes and amplitude and latency of click responses were measured. Wild-type (WT) littermates and Slc10a4 -/- mice also received subanesthetic doses of ketamine (5 mg/kg and 20 mg/kg) to provoke psychomimetic behavior. WT animals showed N40 second click (S2) response amplitude significantly decreased compared to the first click (S1) response under saline and ketamine 5 mg/kg treatments, but not upon ketamine (20 mg/kg) verifying the classic psychomimetic effect of ketamine. Slc10a4 -/- mice instead showed no significant differences between N40 S1 and S2 response amplitudes at any ketamine dose. Auditory gating (S2/S1 ratio) was similar between WT and Slc10a4 -/- mice, however, the negative component (N40) of the aERP showed increased latency while the positive component (P80) showed higher amplitude in Slc10a4 -/- mice compared to WT littermates. This study indicates that both the cholinergic and monoaminergic systems participate in the temporal coding (response latency) of the aERP N40 component, and in the amplitude of the aERP P80 component, thus the Slc10a4 -/- mice could be used to investigate attentional disorders. Taken together, both animals with noise-induced tinnitus and mice lacking the SLC10A4 protein have preserved auditory sensory gating, but impaired auditory sensory processing. The results of this thesis adds knowledge to the identification of electrophysiological signatures for identifying abnormal neuronal networks, which is important for future establishment of clinically relevant biomarkers of brain disorders.